F71. EFFECTS OF EARLY INTERVENTION FOR SERIOUS MENTAL ILLNESS ON SEVERITY OF SYMPTOMATOLOGY. (9th April 2019) - Warner, Alia; Hamilton, Jane; Allen, Melissa
Abstract: Background: Individuals with serious mental illnesses (SMI) often experience substantial disability and associated distress. It is widely hypothesized that early interventions can alter the course of illness and reduce morbidity and mortality if administered within the first five years of onset. Recent literature regarding some psychosocial interventions (e.g., CBT) supports this hypothesis, but many methodological issues limit the existing research. Studies have used heterogeneous interventions and implementations, exclude some serious mental illnesses (e.g., bipolar disorder), and few studies extend beyond the first psychotic episode regardless of the recency of onset. Additionally, few studies investigate inpatient early intervention treatment outcomes for low-income, uninsured individuals with SMI. Examining program outcomes appears of great import, especially among individuals who are already disadvantaged (i.e., indigent). This study describes preliminary symptom severity outcome data from patients that participated in an early onset treatment program in a regional academic safety-net hospital. Methods: Individuals with SMI (schizophrenia-spectrum, major depressive disorder, and bipolar disorder) that participated in an inpatient early onset program (n = 18) were administered severity measures pre- and post-treatment. Patients had an average length of stay of 87 days and were provided various interventions: psychiatry, psychotherapy (individual and group formats), case management, family psychoeducation, and recreation therapy. Individuals with psychotic symptoms were administered the Positive and Negative Syndrome Scale (PANSS), all patients were administered the Severe-Outcome Questionnaire (S-OQ), and when applicable, the Beck Depression Inventory-Second Edition (BDI-II). Pre- to post-treatment change across measures was analyzed using paired samples t-tests on the group level and with clinically significant cut-scores at the individual level. Results: PANSS scores significantly decreased at the completion of treatment. The PANSS total score had a mean reduction of 30.55-points, which was significant (t = 7.410, df = 17, p < .001). Additionally, pre- and post-treatment scores significantly declined on all PANSS scales: positive symptoms (t = 8.076, df = 17, p < .001), negative symptoms (t = 5.182, df = 17, p < .001), and general psychopathology (t = 5.630, df = 17, p < .001). Of the sample, 83% of individuals' PANSS scores decreased more than 20%, indicating clinically significant change. Among patients with a major mood episode, BDI-II scores significantly declined (t = 5.041, df = 8, p = .001), with an average reduction of 25.44-points. S-OQ scores also significantly differed (t = 2.626, df = 17, p =.018), with a mean reduction of 26.11 and 50% of patients exhibiting clinically significant improvement per reliable change index criteria. Discussion: Results provide support to the burgeoning literature on early interventions in SMI and suggest that benefits of early intervention may extent to SMI populations that have been excluded from prior studies, such as major depressive and bipolar disorders. These results also suggest that treatment gains can be substantial among disadvantaged, indigent individuals, despite their numerous challenges (e.g., difficulties with housing, finances, social support, and follow-up care). Confirmatory data are needed and expansion of data collection is underway, including collection of follow-up disability and symptom severity scores.